EFFECT OF SANDY SEDIMENTS PRODUCED BY THE MECHANICAL CONTROL OF SAND DEPOSITION ON THE THERMAL REGIME OF UNDERLYING PERMAFROST ALONG THE QINGHAI‐TIBET RAILWAY. (22nd August 2011) - Xie, s.; Qu, J.; Zu, R.; Zhang, K.; Han, Q.; Niu, Q.
ABSTRACT To date, the mechanical control of drifting sand is the main method used for the protection of the Qinghai‐Tibet Railway from damage. The thermal effect of sandy sediments which are held in place on the underlying permafrost is a key area of interest and the focus of this paper. A ground temperature investigation of the permafrost along the railway route was undertaken and results were related to the different mechanical control measures used to control moving sand which had resulted in varying sandy sediment thicknesses. The studies were conducted in the Hongliang River area of the Qinghai‐Tibet Plateau from June 2010 to September 2010 using thermistor sensors. The results showed that the permafrost ground temperature and its daily variation, as well as the thawing depth of the active layer, decreased after the setting‐up of sand movement controls which had resulted in the accumulation of thick sandy sediments within the outside fringe of sand‐control engineering, or a covering of thin sandy sediments within the inside trackside (fringe) of sand‐control engineering. Below the thick sandy sediment cover accumulated by sand‐blocking fences, the average maximum temperature decreased. Average temperature decreased and the average depth of seasonal thawing (average thinning) were 3·38°C, 0·54°C and 0·48 m, respectively. Below the thin sand sediment cover accumulated by the checkerboard sand barriers, the values for the same parameters were 1·02°C, 0·21°C and 0·5 m, respectively. This study found that the mechanical control of sand does not only protect the railway from obstruction, but also facilitates permafrost stability, which in turn can help promote safety in railway operations. Copyright © 2011 John Wiley & Sons, Ltd.